2021
DOI: 10.3390/molecules26071989
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Collection Volume and DNA Extraction Method on the Detection of Biomarkers and HPV DNA in First-Void Urine

Abstract: The potential of first-void (FV) urine as a non-invasive liquid biopsy for detection of human papillomavirus (HPV) DNA and other biomarkers has been increasingly recognized over the past decade. In this study, we investigated whether the volume of this initial urine stream has an impact on the analytical performance of biomarkers. In parallel, we evaluated different DNA extraction protocols and introduced an internal control in the urine preservative. Twenty-five women, diagnosed with high-risk HPV, provided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The human β-globin ( HBB ) and mgpa allele were used as internal quality controls to ensure the performance of nucleic acid extraction and species identification, respectively. The HBB gene is widely recognized as an internal control gene in human samples that often coexists with target genes in clinical samples ( 41 , 42 ). Because there are only slight differences in the T m value (<0.3°C) between mutations S83N and D87N in the combined products, using assay 2, it is difficult to quickly distinguish between these mutations on samples with poor quality (such as in cases with redundant salt ions and proteins in the sample).…”
Section: Methodsmentioning
confidence: 99%
“…The human β-globin ( HBB ) and mgpa allele were used as internal quality controls to ensure the performance of nucleic acid extraction and species identification, respectively. The HBB gene is widely recognized as an internal control gene in human samples that often coexists with target genes in clinical samples ( 41 , 42 ). Because there are only slight differences in the T m value (<0.3°C) between mutations S83N and D87N in the combined products, using assay 2, it is difficult to quickly distinguish between these mutations on samples with poor quality (such as in cases with redundant salt ions and proteins in the sample).…”
Section: Methodsmentioning
confidence: 99%
“…GenPlex ® HPV genotyping assay could realize many sample-in-result-out multiplexed molecular detection. In one test, 24 HPV genotypes can be detected and genotyped simultaneously (HPV 6,11,16,18,31,33,35,39,42,43,44,…”
Section: Hpv Detectionmentioning
confidence: 99%
“…Currently, most studies determined the potential of available HPV tests applied in urine which had been developed for cervical samples 12–14 . As expected, a discrepancy in the findings has been observed, indicating a lack of standardized HPV tests for urine 15,16 . Considering the lower viral load in urine compared with the cervical exfoliated sample, real‐time polymerase chain reaction (PCR) based HPV tests could improve the performance of HPV detection in urine and reduce variability than other ones 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urinary cfDNA was extracted from 20 mL (patients) or 40 mL (controls) urine supernatant using the Quick DNA urine kit (Zymo Research, Irvine, CA, US). Previous research showed that differences in urine collection volume in a similar range (4-20 mL) have limited effects on DNA yield, eliminating this potential bias [26]. DNA concentration was measured using the Qubit™ dsDNA HS Assay (Invitrogen, Carlsbad, CA, US).…”
Section: Cell-free Dna Extraction and Bisulfite Conversionmentioning
confidence: 99%